SOSIALISASI PERAN PERGURUAN TINGGI DAN AKADEMISI SEBAGAI INKUBATOR BISNIS DALAM PENGUATAN KOPERASI SEBAGAI LEMBAGA EKONOMI KERAKYATAN MENUJU KOPERASI MODERN BAGI PELAKU UKM DI SUMATERA UTARA - Ulung Napitu; Corry Corry; Anggiat Sinurat; Tuangkus Harianja; Ease Arent; Mardiani Mardiani; Ade Mey Lisca Nasution; Hasian Napitu (Jurnal Pengabdian Masyarakat Sapangambei Manoktok Hitei, 2022)
This community service aims to provide an understanding that universities and academics act as business incubators for developing small and medium enterprises. In order to support the growth and development of SMEs, there needs to be a synergy from various parties ranging from academia, industry, and universities as stakeholders. The business incubator is a place used by many developing countries, including Indonesia, as a means of developing new businesses and/or small and medium enterprises (SMEs). The business incubator itself is an institution that oversees a business incubation in the coaching process for small businesses and/or new product development as well as the provision of business facilities and infrastructure, business development, and management and technology support. The availability of skilled labor needed by the Business and Work World (DUKA) is still very low. This is revealed from data from the Central Statistics Agency (BPS) which was announced in February 2020, which was around 13%. This condition is a challenge for universities not to exacerbate this condition by introducing an early work environment to students, so that they can become graduates according to the needs of the job market, either as employees or business owners through student business incubators at universities.The Business Incubator is a form of Academic Entrepreneurship adapted to the industrial era 4.0 based on the use of electronic media and the internet. To socialize the community service material to SME business actors, the lecture method and question-and-answer method are used for 90 minutes. The results of the socialization have further increased the understanding of the community and SMEs about the importance of developing business incubators as business facilities and infrastructure in business development.